2024
DOI: 10.3390/molecules29020446
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazole-Based Derivatives as Apoptotic Antiproliferative Agents: Design, Synthesis, Docking, and Mechanistic Studies

Bahaa G. M. Youssif,
Martha M. Morcoss,
Stefan Bräse
et al.

Abstract: A new class of benzimidazole-based derivatives (4a–j, 5, and 6) with potential dual inhibition of EGFR and BRAFV600E has been developed. The newly synthesized compounds were submitted for testing for antiproliferative activity against the NCI-60 cell line. All newly synthesized compounds 4a–j, 5, and 6 were selected for testing against a panel of sixty cancer cell lines at a single concentration of 10 µM. Some compounds tested demonstrated remarkable antiproliferative activity against the cell lines tested. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Benzimidazoles are well known nitrogen-containing bioactive compounds. They showed a variety of activities including anti-diabetic [ 1 ], antimicrobial [ 2 ], antifungal [ 3 ], antiviral [ 4 ], anti-cancer activity [ [5] , [6] , [7] ] (including anti breast cancer [ 8 ]) and anthelminthic [ 9 ]. Recent studies in medicinal chemistry have demonstrated them as potential drug motifs for the pharmaceutical industry [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benzimidazoles are well known nitrogen-containing bioactive compounds. They showed a variety of activities including anti-diabetic [ 1 ], antimicrobial [ 2 ], antifungal [ 3 ], antiviral [ 4 ], anti-cancer activity [ [5] , [6] , [7] ] (including anti breast cancer [ 8 ]) and anthelminthic [ 9 ]. Recent studies in medicinal chemistry have demonstrated them as potential drug motifs for the pharmaceutical industry [ 10 ].…”
Section: Introductionmentioning
confidence: 99%